2013
DOI: 10.1016/j.mejo.2013.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic voltage scaling for series hybrid amplifiers

Abstract: We present an optimization of the voltage scaling algorithm in low power audio class G amplifier for headphones application to allow longer playback time. The optimization approach minimizes the voltage difference between the internal audio amplifier power supply and its output signal over a large range of operating conditions. The modeling is based on a behavioral model enabling accurate and rapid evaluation of efficiency and audio quality with realistic input stimuli. The model validated in practice is used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…In addition, at this current level the magnetic material is saturated, but in fact, at current levels lower than the component rated current, the material would also be saturated (saturation appears for currents higher than 20 mA). Note also that in real audio signals, the crest factor (crest f actor = peak value/rms value) is generally higher than the one of a sinusoidal signal [33]. The peak value is then considerably higher than the rms current.…”
Section: Time Domain Simulationsmentioning
confidence: 97%
“…In addition, at this current level the magnetic material is saturated, but in fact, at current levels lower than the component rated current, the material would also be saturated (saturation appears for currents higher than 20 mA). Note also that in real audio signals, the crest factor (crest f actor = peak value/rms value) is generally higher than the one of a sinusoidal signal [33]. The peak value is then considerably higher than the rms current.…”
Section: Time Domain Simulationsmentioning
confidence: 97%
“…Therefore, due to the EMI filter, the system consumes 5 times more at low output power. In [2], it has been shown that in a real audio signal (i.e. Jazz song), there are more amplitude levels lower than -20 dB full scale than the higher amplitudes for a 10 s recording.…”
Section: Introductionmentioning
confidence: 99%